2016
DOI: 10.1002/jcp.25397
|View full text |Cite
|
Sign up to set email alerts
|

SRC Family Kinase Inhibition in Ewing Sarcoma Cells Induces p38 MAP Kinase-Mediated Cytotoxicity and Reduces Cell Migration

Abstract: Ewing sarcoma (ES) is a highly aggressive bone and soft tissue cancer, representing the second most common primary malignant bone tumor in children and adolescents. Although the development of a multimodal therapy, including both local control (surgery and/or radiation) and systemic multidrug chemotherapy, has determined a significant improvement in survival, patients with metastatic and recurrent disease still face a poor prognosis. Moreover, considering that ES primarily affects young patients, there are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
5
14
0
Order By: Relevance
“…SRC is a proto-oncogene that is aberrantly activated in most types of cancer [29], which is consistent with our results showing that SRC is significantly increased in both cell types. Further, the FAK-SRC signaling pathway regulates the invasion of lung cancer [30] and Ewing sarcoma cells [29], indicating that SRC may be a key therapeutic target for cancer treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SRC is a proto-oncogene that is aberrantly activated in most types of cancer [29], which is consistent with our results showing that SRC is significantly increased in both cell types. Further, the FAK-SRC signaling pathway regulates the invasion of lung cancer [30] and Ewing sarcoma cells [29], indicating that SRC may be a key therapeutic target for cancer treatment.…”
Section: Discussionsupporting
confidence: 93%
“…SRC is a proto-oncogene that is aberrantly activated in most types of cancer [29], which is consistent with our results showing that SRC is significantly increased in both cell types. Further, the FAK-SRC signaling pathway regulates the invasion of lung cancer [30] and Ewing sarcoma cells [29], indicating that SRC may be a key therapeutic target for cancer treatment. It is widely accepted that all modes of migration require RHO GTPase, including RHO and CDC42 (Fig 4A and 4B) due to its effects on the regulation of actin dynamics that plays a critical role in cell migration depending on the environment [31, 32].…”
Section: Discussionsupporting
confidence: 93%
“…For example, dasatinib is believed to affect YAP/TAZ primarily through targeting SRC [251]. Studies in both osteosarcoma and Ewing sarcoma cell lines reported inhibition of the migration and induction of apoptosis by dasatinib [252,253].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cAMP signaling interacts with other intracellular signaling pathways, including cytokine and Ras‐Raf‐ Erk pathways (Follin‐Arbelet et al, ; Spina et al, ; Tai et al, ; Cheng et al, ; Park and Juhnn, ). Notably, these signaling connections also play an important role in cancer biology and a combined blockade of such signaling pathways is considered a relevant strategy for therapeutic intervention to fight cancer (Awada and Aftimos, ; Indovina et al, ; Kidger and Keyse, ).…”
Section: A Glance At Camp Signalingmentioning
confidence: 99%